Paralinguistic Features as Indicators of Meaning in English Spoken Communication - Raximova Nargiza Ulugbekovna; Abduazizova D.A (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Paralinguistic features play a crucial role in enhancing the meaning of spoken communication beyond mere verbal content, particularly in English. These non-verbal elements, including tone, pitch, volume, pace, rhythm, pauses, gestures, and facial expressions, convey emotions, intentions, and contextual nuances that shape listener interpretations. This study explores the theoretical foundations, types, and functions of paralinguistic features in English spoken discourse, drawing comparisons with Uzbek linguistics to highlight cross-cultural variations. Through a literature review and analysis of examples from English and Uzbek sources, the research demonstrates how these features influence evaluative judgments, persuasion, and intercultural understanding. The findings underscore the importance of paralinguistics in effective communication, emphasizing their role in economizing speech, expressing emotions, and facilitating mutual comprehension. By integrating insights from global and Uzbek scholarship, this work contributes to a deeper appreciation of non-verbal cues in multilingual contexts, advocating for their inclusion in language teaching and cross-cultural studies.